Electronic Word of Mouth (E-Wom) of Transportation Application Consumers in Indonesia: Which Factors That Are Matter - L. Leonnard; Etty Susilowati (Esensi: Jurnal Bisnis dan Manajemen, 2018)
Transportation applications are now becoming a popular means of transportation in major cities of developing countries. This is because high levels of community mobility are faced with high levels of congestion. This study was constructed to test the effect of service quality to e-WOM through consumer satisfaction by using PLS SEM-path modeling. Empirical findings indicated that all hypotheses tested are proven. Service quality had a significant positive effect directly on satisfaction and indirectly against e-WOM. Subsequently, from the service quality indicator, the most influential indicator was the driver interaction with the consumer. These findings were different from public transportation, which did not employ online application where indicator tangibles had the highest effect that create consumer perception of service quality. Discussion and managerial implications are provided.DOI: 10.15408/ess.v8i1.6708